"An Exhibit as Will Astonish the Civilized World": Seeking Separate Statehood for Indian Territory at the 1904 Louisiana Purchase Exposition. (January 2023) - Crossley, Laura
Abstract: Chickasaw, Choctaw, Cherokee, Muscogee, and Seminole citizens employed the Indian Territory exhibits at the 1904 Louisiana Purchase Exposition to advance the separate statehood movement. Increasingly shut out of the formal political realm, they adopted creative measures to exert their political will, including participating in the world's fair. Employing insights from settler-colonial theory and public history, this paper argues that the politics of display expanded the agency of a group marginalized from political representation. The U.S. government, pressured by the territory's growing population of non-Native settlers, had begun planning for statehood, passing the 1898 Curtis Act to force allotment and dissolve the Five Tribes' governments by 1906. To protect their land and sovereignty, a cohort of Native citizens pursued statehood for Indian Territory separate from Oklahoma Territory. Although joint statehood won out, separate statehood advocates succeeded in creating exhibits that centered on the survival of Native nations. They also articulated an Indigenous conception of citizenship, developing an imaginative vision for a future in which self-determination and U.S. citizenship could converge in a Native state. This represented a novel contribution to ongoing debates over how to integrate remaining western territories into the United States and how to incorporate diverse peoples within the citizenry.